Implementation of trot-to-gallop transition and subsequent gallop on the MIT Cheetah I - Hyun, Dong Jin; Lee, Jongwoo; Park, SangIn; Kim, Sangbae (SAGE PUBLICATIONS LTD, 2016)
This paper presents a demonstration of the trot-to-gallop transition and subsequent stable gallop in a robotic quadruped. The MIT Cheetah I, a planar quadruped platform for high-speed running, achieves these tasks with a speed of 3.2 m/s (Froude number of 2.1) on a treadmill. The controller benefits from clues from biological findings and it incorporates (1) a gait pattern modulation that imposes predefined gait patterns with a proprioceptive touchdown feedback, (2) tunable equilibrium-point foot-end trajectories for four limbs that intentionally modulate ground reaction forces, and (3) programmable leg compliance that provides instantaneous reflexes to leg-ground interaction. An inertial measurement unit sensor is integrated with the controller in order to regulate leg angles of attack at touchdown. We reduce the dimension of the control parameters which describe temporal/spatial characteristics of quadruped locomotion, and the values are tuned via dynamic simulation and then experiment. Given a pre-defined virtual leg compliance and a desired angle of attack of legs, the equilibrium-point foot-end trajectories and phase relationships between four legs for stable trot and gallop gaits are found independently. We propose a simple throw-and-catch gait transition strategy which connects two stable limit cycles, the trot and the gallop, by linearly varying control parameters during the transition period. Successful gait transition is achieved in both simulation and experiment. Comprehensive analysis on the characteristics of the MIT Cheetah I experimental trot-to-gallop transition is provided. The phase portraits imply that stable limit cycles are achieved with the proposed controller in both trot and gallop, which enables the trot-to-gallop gait transition at high speed.
Keywords: IMPEDANCE CONTROL; QUADRUPED ROBOT; ENERGETIC COST; GAIT; LOCOMOTION; TRANSVERSE; STABILITY; DYNAMICS; CONTACT; WALKING